Estudio de prevalencia de mucositis oral en pacientes oncológicos adultos bajo quimioterapia que acuden a Solca – Loja en el periodo Septiembre – Diciembre 2022 - Encarnación Hidalgo, Brailyn Leonel (2023)
Oral mucositis is one of the main side effects in patients undergoing chemotherapy, characterized by the presence of ulcerative and erythematous lesions that cause taste disturbances, dysphagia, and adversely affect the quality of life. Therefore, the purpose of this research was to determine the prevalence of oral mucositis in oncology patients undergoing chemotherapy at the Solca Cancer Institute in the city of Loja. Additionally, it aimed to investigate the influence of the number of chemotherapy cycles and pharmacological doses on the occurrence of oral mucositis. This was accomplished through an analytical, cross-sectional case-control study conducted on 16 patients undergoing chemotherapy with a follow-up of four months. The research utilized a dental medical history developed and approved by Solca for the research project to attend the patients of Solca Núcleo Loja.The results of this study showed that 50% of patients undergoing chemotherapy presented oral mucositis. However, there was no significant difference in the occurrence of this condition concerning the number of cycles and dosages of antineoplastic drugs. In conclusion, chemotherapy can indeed affect oncology patients by causing oral mucositis. Nevertheless, it cannot be definitively stated or refuted that the number of cycles and pharmacological dosages contribute to the incidence of oral mucositis in patients receiving chemotherapy